Participation rate of farmers in different multifunctional activities in the Netherlands. (September 2016) - Hassink, Jan; Agricola, Herman; Thissen, Jac
In this article, we present the findings from a study into the relationships between socio demographic, economic, and geographical characteristics of farm holdings and their participation rate in multifunctional activities. Recreation, nature management, care, and education services are most widespread among dairy farms. Farm holders of arable and dairy farms with extended activities are younger and the economic size of their enterprises is larger than that of conventional enterprises. For horticultural and intensive husbandry farmers, there were no age differences and, unlike the land-based types of holdings, the economic size of farms with extended activities was smaller than that of conventional farms. While care and education are more widespread in urbanized areas, the opposite was found for nature management. Proximity to sea has a positive impact on the participation rate in recreation, on-farm selling, and nature management. In order to understand the decisions of farmers, it is crucial to take the type of multifunctional activity, type of agricultural holding, and location into consideration.